Sustainable Web Ecosystem Design - O'Toole, Greg (SpringerBriefs in Computer Science,, 2013)
This book is about the process of creating web-based systems (i.e., websites, content, etc.) that consider each of the parts, the modules, the organisms - binary or otherwise - that make up a balanced, sustainable web ecosystem. In the current media-rich environment, a website is more than a collection of relative html documents of text and images on a static desktop computer monitor. There is now an unlimited combination of screens, devices, platforms, browsers, locations, versions, users, and exabytes of data with which to interact. Written in a highly approachable, practical style, this book is useful for stakeholders, system administrators, developers, designers, content managers, and the anonymous web user in industry, as well as faculty, staff, and students of all levels involved in teaching and learning in information technology.